Decreased Endomorphin-2 and μ-Opioid Receptor in the Spinal Cord Are Associated with Painful Diabetic Neuropathy - Kou, Zhen-Zhen; Wan, Fa-Ping; Bai, Yang; Li, Chun-Yu; Hu, Jia-Chen; Zhang, Guo-Tao; Zhang, Ting; Chen, Tao; Wang, Ya-Yun; Li, Hui; Li, Yun-Qing (Frontiers in Molecular Neuroscience, 2016)
Painful diabetic neuropathy (PDN) is one of the most common complications in the early stage of diabetes mellitus (DM). Endomorphin-2 (EM2) selectively activates the opioid receptor (MOR) and subsequently induces antinociceptive effects in the spinal dorsal horn. However, the effects of EM2-MOR in PDN have not yet been clarified in the spinal dorsal horn. Therefore, we aimed to explore the role of EM2-MOR in the pathogenesis of PDN. The main findings were the following: (1) streptozotocin (STZ)-induced diabetic rats exhibited hyperglycemia, body weight loss and mechanical allodynia; (2) in the spinal dorsal horn, the expression levels of EM2 and MOR decreased in diabetic rats; (3) EM2 protein concentrations decreased in the brain, lumbar spinal cord and CSF in diabetic rats but were unchanged in the plasma; (4) the frequency but not the amplitude of spontaneous excitatory postsynaptic currents (sEPSCs) was significantly higher in diabetic rats than in control rats; and (5) intrathecal injection of EM2 for 14 days in the early stage of PDN partially alleviated mechanical allodynia and reduced MOR expression in diabetic rats. Our results demonstrate that the EM2-MOR signal may be involved in the early stage of PDN.